Outcomes after lung transplantation - Thabut, Gabriel; Mal, Herve (Journal of Thoracic Disease, 2017)
With more than 50,000 procedures having been performed worldwide, lung transplantation (LT) has become the standard of care for patients with end-stage chronic respiratory failure. LT leads to dramatic improvements in both pulmonary function and health related quality of life. Survival after LTs has steadily improved, but still lags far behind that observed after other solid organ transplantations, as evidenced by a median survival rate that currently stands at 5.8 years. Because of these disappointing results, the ability of LT to expand survival has been questioned. However, the most recent studies, based on sophisticated statistical modeling suggest that LT confers a survival benefit to the vast majority of lung transplant recipients. Chronic lung allograft dysfunction (CLAD) that develops in about 50% of recipients 5 years after LT is a major impediment to lung transplant survival. A better understanding of the mechanisms underlying CLAD could allow for better post-transplant survival.